State, institutions and competitiveness : the urgency of institutional capacity-building in Jamaica - Hughes, Wesley George (2008)
Uses developments from Jamaica' s past to demonstrate the impact of state policies, which reflect varying degrees of institutional capacity, on the country's development. Suggests a new institutional path if Jamaica is to be propelled towards an era of competitiveness, sustainable growth and balanced development.